Planet(esimal)s around stars with TESS (PAST) III: A search for triplet He i in the atmospheres of two 200 Myr-old planets. Issue 3 (12th November 2022) - Gaidos, Eric; Hirano, Teruyuki; Lee, Rena A; Harakawa, Hiroki; Hodapp, Klaus; Jacobson, Shane; Kotani, Takayuki; Kudo, Tomoyuki; Kurokawa, Takashi; Kuzuhara, Masayuki; Nishikawa, Jun; Omiya, Masashi; et al.
ABSTRACT: We report a search for excess absorption in the 1083.2 nm line of ortho (triplet) helium during transits of TOI-1807b and TOI-2076b, 1.25 and 2.5- R ⊕ planets on 0.55- and 10.4-d orbits around nearby ∼200 Myr-old K dwarf stars. We limit the equivalent width of any transit-associated absorption to <4 and <8 mÅ, respectively. We limit the escape of solar-composition atmospheres from TOI-1807b and TOI-2076b to ≲1 and ≲0.1 M ⊕ Gyr −1, respectively, depending on wind temperature. The absence of a H/He signature for TOI-1807b is consistent with a measurement of mass indicating a rocky body and the prediction by a hydrodynamic model that any H-dominated atmosphere would be unstable and already have been lost. Differential spectra obtained during the transit of TOI-2076b contain a He i -like feature, but this closely resembles the stellar line and extends beyond the transit interval. Until additional transits are observed, we suspect this to be the result of variation in the stellar He i line produced by rotation of active regions and/or flaring on the young, active host star. Non-detection of escape could mean that TOI-2076b is more massive than expected, the star is less EUV luminous, the models overestimate escape, or the planet has a H/He-poor atmosphere that is primarily molecules such as H2 O. Photochemical models of planetary winds predict a semimajor axis at which triplet He i observations are most sensitive to mass-loss: TOI-2076b orbits near this optimum. Future surveys could use a distance criterion to increase the yield of detections.